Advances and applications in model-driven engineering - García Díaz, Vicente, 1981-; Cueva Lovelle, Juan Manuel; Pelayo García-Bustelo, Begona Cristina, 1971-; Sanjuán Martínez, Oscar (Information Science Reference, 2014)
"This book explores this relatively new approach in software development that can increase the level of abstraction of the development of tasks, bridging the gaps between various disciplines within software engineering and computer science"--Provided by publisher.
Keywords: Engineering models.; elektronické knihy; electronic books